Design and Application of a New Acid-Alkali-Surfactant Flooding Formulation for Malaysian Reservoirs - Khaled , A. Elraies (Society of Petroleum Engineers, 2010)
A new Acid-Alkali-Polymeric Surfactant (AAPS) flooding formulation has been developed to overcome the precipitation problems caused by the divalent metal cations prevalent with conventional ASP flooding. The acid was evaluated in an acid-alkali-surfactant formulation using sodium carbonate and introducing a new polymeric surfactant derived from Jatropha oil. The effect of the new formula on IFT, viscosity, and oil recovery was studied using natural seawater having a large quantity of divalent metal cations. The tolerance of the AAPS towards natural untreated sea water was monitored for 90 days at 90 oC. No precipitations were formed with the acid additive, while precipitations were always generated without the acid. A combination of the new system was found to significantly reduce the IFT between Angsi crude oil and AAPS solution. The most outstanding feature of the AAPS formulation lies in its viscosity insensivity towards an increasing alkali concentration up to 1.2%. Core flood tests with alkali and acid concentrations of 0.6% and 1% respectively confirmed an optimum surfactant concentration of 0.6%. Using the optimum AAPS concentrations, another series of core flood were conducted by changing the injection volume. Only a small incremental recovery was obtained with AAPS slugs higher than 0.5 PV. Injection of 0.5 PV of the formulated AAPS slug followed by chase water produced an additional 18.8% OOIP over water flooding. The benefit of the new system is the use of seawater rather than softened water while maintaining the desired slug properties.